Determinants of Egypt’s Food Imports Based on Vector Error-Correction Model (VECM) - Agbo, Hanan Mahmoud Sayed (European Journal of Sustainable Development, 2022)
The issue of food and the provision of society’s needs have a priority in the Egyptian economic policy. Therefore, the state tends to import large quantities of these commodities annually from the global market to bridge the gap between consumption and domestic production. This study focuses on determining the main factors that affect Egyptian food imports during the period 1990–2019, using a Vector Error-Correction Model (VECM) that will help policymakers use the appropriate monetary, fiscal, and trade tools to manage Egypt’s food imports and decrease the import cost. The empirical results revealed that the most important factors’ effects on Egypt’s food imports are population growth and inflation rate, but imported food prices and GDP per capita have an effect only in the long run. On the other hand, there are no significant effects of the foreign reserves, exchange rate, and agricultural production on food imports.